IMPLEMENTASI SISTEM MONITORING PEMOSISI GLOBAL TRANSPORTASI DARAT BERBASIS ESP32 DENGAN KOMUNIKASI LORA - Alpharisy, Kevin Farid; Soim, Sopian; Hadi, Irawan (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
Navigation technology has become an important component in everyday life, the development of the Internet of things (IoT) technology increases with the human need for a system that can work reliably in making work easier. The purpose of this study is to produce a simple tracking system that can be used on mobile vehicles or public transportation so that it helps the public to receive information about the position of public transportation so as to make time efficient, can also be used as a security system on private vehicles. Previously, the Tracker Development used WiFi technology or sim module, the WiFi range was considered to be very small, less than 50m and the sim module was less efficient therefore there must be renewed. This system was built using the ESP32 microcontroller and the LoRa Antares communication system. it works on the 920-923 MHz channel frequency. This system works with the GPS module as a receiver for position information based on triangulation of several satellites in space, devices that are within the reach of the LoRa gateway will send data to the web server antares. Then the data is processed and displayed visually to the dashboard. The average shipping delay is 1.1 seconds, the maximum delay is 8 seconds, the minimum delay is 0 seconds, packet loss is 23%, the maximum radius is 2.16KM. Data was collected at PT Telkom DDS Gegerkalong Hilir, Bandung.